Inter-capsular resection of cervical vagus nerve schwannoma. (August 2018) - Kuroiwa, Masafumi; Yako, Takehiro; Goto, Tetsuya; Higuchi, Kayoko; Kitazawa, Kazuo; Horiuchi, Tetsuyoshi; Kobayashi, Shigeaki
Highlights: Cervical vagus nerve schwannoma should be removed while preserving neural function. "Inter-capsular resection" method is a safe and reliable technique for the tumor. Basic steps of the method are explained with schemas. The layer of true tumor capsule was histopathologically proved. Abstract: Cervical vagus nerve schwannoma is rare and its surgical procedure is controversial. The tumor is in general benign and slowly growing without causing symptoms, and therefore it should be advised to remove the tumor while preserving neural function. We operated on two patients with cervical vagus nerve schwannoma with the inter-capsular resection technique proposed by Hashimoto et al. without causing neurological deficits. It is the first time that the plane between the tumor-complex capsule layer (epineurium and perineurium) and true tumor capsule layer was histopathologically proved in this paper. The true tumor capsule layer contained no normal neural fibers, tumor tissues and neural sheath. The inter-capsular resection technique is a safe and reliable method for removing cervical vagus nerve schwannoma.